2014
DOI: 10.1016/j.microrel.2014.07.119
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of thick Al wire: A study of the effects of wire bonding parameters on thermal cycling degradation rate using non-destructive methods

Abstract: Access from the University of Nottingham repository:http://eprints.nottingham.ac.uk/36483/1/Reliability%20of%20thick%20Al%20wire%20A %20study%20of%20the%20effects%20of%20wire%20bonding%20parameters%20on %20thermal%20cycling%20degradation%20rate%20using%20non-destructive %20methods.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the Creative Commons Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…Our previous research confirmed that the current envelope of the electrical signal reflects the wire bonding machine parameters, and the correlation between the bond signal characteristics and the bond quality was confirmed by X-ray tomography images [11]. In this paper, this correlation between is examined for subtle change in bonding conditions, using a semisupervised learning algorithm.…”
Section: Feature Selection and Classification Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…Our previous research confirmed that the current envelope of the electrical signal reflects the wire bonding machine parameters, and the correlation between the bond signal characteristics and the bond quality was confirmed by X-ray tomography images [11]. In this paper, this correlation between is examined for subtle change in bonding conditions, using a semisupervised learning algorithm.…”
Section: Feature Selection and Classification Methodssupporting
confidence: 61%
“…In our previous work [11], we demonstrated a clear link between differences in bond quality arising from the changes in wire bonding parameters and the characteristics of the current envelope of the ultrasonic signals obtained from the transducer. In this paper, we examine whether the above method can be used to discriminate subtle quality differences arising from bonds made from the same parameters (e.g., as on a typical manufacturing line).…”
mentioning
confidence: 84%
“…There are two popular ways to assemble a discrete HEMT on a carrier: wire bonding and flip‐chip. The conventional wire‐bonding is more common; however, it suffers from several shortcomings such as the wire inductance effects, discontinuities, nonreproducible wire‐bonds, and low reliability of interconnects due to the thermo‐mechanical stress . Currently, the flip‐chip technique with electrical and mechanical bumping has become prevalent as an alternative method for conventional wire‐bonding assembly.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional wire-bonding is more common; however, it suffers from several shortcomings such as the wire inductance effects, discontinuities, nonreproducible wire-bonds, and low reliability of interconnects due to the thermo-mechanical stress. [8][9][10][11] Currently, the flip-chip technique with electrical and mechanical bumping has become prevalent as an alternative method for conventional wire-bonding assembly. In this technique, transistor is mounted upside-down with bottom plate suspended in the air.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding strength is often estimated with the bonded area. The bonded area was visualized by ultrasonic C-scan testing [12][13][14][15] and radiography [16,17]. In these studies, it was indicated that the relation between the bonded area and the bonding strength are linearly correlated.…”
Section: Introductionmentioning
confidence: 99%